The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00586-006-0235-4
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle growth asymmetry as a cause of adolescent idiopathic scoliosis: a biomechanical study

Abstract: Over the last century the neurocentral junction (NCJ) has been identified as a potential cause of adolescent idiopathic scoliosis (AIS). Disparate growth at this site has been thought to lead to pedicle asymmetry, which then causes vertebral rotation and ultimately, the development of scoliotic curves. The objectives of this study are (1) to incorporate pedicle growth and growth modulation into an existing finite element model of the thoracic and lumbar spine already integrating vertebral body growth and growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 25 publications
0
22
1
2
Order By: Relevance
“…Further, the relative motion between vertebrae was monitored to ensure segmental motion remained within physiologic range. Moreover, it was previously demonstrated that irregular pedicle growth did not produce scoliotic curves in a FEM [12]. Nevertheless, the authors recognize that if a contact between posterior elements occurred it may influence local relative displacements between adjacent segments.…”
Section: Discussionmentioning
confidence: 84%
“…Further, the relative motion between vertebrae was monitored to ensure segmental motion remained within physiologic range. Moreover, it was previously demonstrated that irregular pedicle growth did not produce scoliotic curves in a FEM [12]. Nevertheless, the authors recognize that if a contact between posterior elements occurred it may influence local relative displacements between adjacent segments.…”
Section: Discussionmentioning
confidence: 84%
“…In the coronal plane, the centers of gravity were hypothetically assumed to be positioned along the scoliotic spine curve [2,10,29]. The influence of this simplifying hypothesis was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Computer models have been used to analyze the biomechanics of asymptomatic [1,15,18,24,25,31] and scoliotic spines [2,6,10,26,27,29]. To compute the stresses in the scoliotic spine, the gravitational forces were generally included in the models and sometimes an assumption about the muscles contribution was made.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered important for vertebral growth in the transverse plane [3,4,6,14,20]. NCS growth asymmetry can produce an axial deformity, which may result in three-dimensional deformity of the spine (scoliosis) [1,5,10,12,13]. We previously demonstrated a unilateral pedicle screw fixation, which traverses the NCS in an immature pig model, produced NCS epiphysiodesis on the operative side resulting in scoliosis with the convexity on the side of the screw fixation resulting from continued growth of the unaffected side [18].…”
Section: Introductionmentioning
confidence: 99%